AFFIRMATIVE ACTIONS AND PRINCIPLES OF NON DISCRIMINATION - Palestina Salma Subagdja (CV. RADJA PUBLIKA, 2025)
Due to gender construction in society, women are always placed in a lower position than men. This makes women vulnerable to discrimination and injustice. The Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) then made provisions in the form of affirmative action to increase de facto equality between men and women. However, the regulation of this affirmative action conceptually seems contradictory to the principle of non-discrimination in the Universal Declaration of Human Rights (UDHR) as the reference norm of CEDAW which basically does not want any difference in treatment for each person. For this reason, this study will examine affirmative action in CEDAW in relation to the conditions of women and will also examine whether the affirmative action deviates from the principle of non-discrimination in the UDHR. In this study, the problem is examined using the Juridical-Normative research method and it is known that the condition of women is closely related to the provision of affirmative action. In addition, it is also known that the regulation regarding affirmative action against women is not a deviation from the principle of non-discrimination and cannot be categorized as a form of discrimination as referred to in Article 2 of the Universal Declaration of Human Rights.